EFEK PENGANGGARAN TERHADAP KINERJA DOSEN PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI DI ACEH - Yusaini Yusaini; Darmawati Darmawati; Zainal Abidin; M. Fadli (UNIVERSITAS INDRAPRASTA PGRI, 2021)
This article aims to discuss one result of research on the response of lecturers to higher education budgeting and the response of lecturers to their performance so far implemented and to determine whether budgeting has a positive effect on lecturer performance in the Aceh State Islamic Religious College (PTKIN). Data collection was carried out at five PTKIN in Aceh, namely UIN Ar-Raniry Banda Aceh, IAIN Langsa, IAIN Lhokseumawe, STAIN Meulaboh, and STAIN Takengon. The population and sample were derived from the lecturers' is data in the staffing section of each PTKIN Aceh, and then determined using the Slovin formula. The type of research chosen is the Mix Method, using descriptive statistics and hypothesis testing using simple regression. The results of the analysis found that the lecturers gave a good response to the budgeting carried out by the team at PTKIN Aceh and the performance results practiced by the PTKIN Aceh lecturers were also good. Meanwhile, the results of hypothesis testing found that there was no significant effect of budgeting on the performance of PTKIN lecturers in Aceh province.